Penerapan aplikasi digital dalam penyusunan laporan keuangan pada usaha mikro: Studi kasus pada 7W Coffee - Pontoh, Natasha Maria Angela; Gamaliel, Hendrik; Kapojos, Peter M. (Yayasan Widyantara Nawasena Raharja, 2024)
Information technology has a significant impact on Accounting Information Systems (AIS) in Micro, Small and Medium Enterprises (MSMEs). One application that has been developed is